Elementary teachers’ understanding of STEM integration: A study in the Indonesia – Malaysia border area - Saputro, Totok Victor Didik; Sari, Yessi Fatika; Silvester; Cahyaningtyas, Christian; Pery Jayanto; Harmoni, Grecia Putri (Universitas Hamzanwadi, 2025)
Science, Technology, Engineering, and Mathematics (STEM) education is vital in preparing students to face future challenges by fostering critical thinking and problem-solving skills. However, in border areas such as Indonesia and Malaysia, the implementation of STEM education remains underexplored. This study uses a quantitative descriptive-comparative design to analyze school teachers' understanding of STEM implementation. It involves 44 teachers from the Indonesia-Malaysia border area in Bengkayang Regency, West Kalimantan, Indonesia. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics and an independent t-test to assess and compare teachers' levels of understanding. The findings indicated moderate scores for STEM knowledge (3.84), implementation practices (3.71), and school support (3.66), while challenges scored low (2.98). In terms of teaching experience, there was no significant difference between teachers with less than 10 years and those with more than 10 years of experience concerning their understanding of STEM implementation in elementary schools. This is attributed to the limited availability of training programs that could enhance teachers' knowledge regarding STEM education.